2012
DOI: 10.4103/2230-8229.98305
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices in the rural population of north India

Abstract: Background:Breastfeeding is one of the most important determinants of child survival, birth spacing, and the prevention of childhood infections. The beneficial effects of breastfeeding depend on its initiation, duration, and the age at which the breastfed child is weaned. Breastfeeding practices vary among different regions and communities.Objectives:To assess the pattern of infant feeding and its relation to certain practices of maternity and newborn care, and to assess the knowledge of mothers on the advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
65
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 18 publications
8
65
3
Order By: Relevance
“…In other studies by Mahmood et al 84.6% of the mothers fed colostrum. 17 However, we found in our study that still a larger percentage (33.34%) of women did not fed colostrum to their baby due to their perception that it is very heavy for baby to digest.…”
Section: Discussioncontrasting
confidence: 47%
“…In other studies by Mahmood et al 84.6% of the mothers fed colostrum. 17 However, we found in our study that still a larger percentage (33.34%) of women did not fed colostrum to their baby due to their perception that it is very heavy for baby to digest.…”
Section: Discussioncontrasting
confidence: 47%
“…Unfortunately, most of these studies have found that the mothers are not aware themselves, that prelacteal feeds could be a source of infection. 6 In our study too, the mothers agreed to give the prelacteal feed because of the prevailing social custom.…”
Section: Discussionmentioning
confidence: 68%
“…6 Also, it was observed that most of the mothers with higher education or from higher income group did not follow the proper breastfeeding practices. Families who can afford cow's milk or formula feed, often introduce bottle feeding before six months perceiving it to be better and healthier than breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 But another study conducted in rural areas by Mahmood SE et al found that only 22% mothers initiated breast feeding within 1 hour. 16 In our study baby separation was found to be the commonest reason (45.05%) for delayed initiation of breastfeeding among the mothers. Wagh S et al observed that most common cause of delay in initiation in breast feeding were caesarean section and delivery complication.…”
Section: Discussionmentioning
confidence: 93%
“…Medhi GK et al also observed late introduction of complementary feeding among the infants in Assam. 16,19,28 Ulak M et al also reported that 79% infants were introduced to complementary food before six months of age and the main reason was assumed insufficient breast milk production. 29 Holambe VM et al observed in their study that late introduction of complementary food was associated with maternal age, education and parity.…”
Section: Discussionmentioning
confidence: 99%